Konsili Trente: Upaya Gereja Katolik Menjawab Tantangan Martin Luther - Marsianus, Marsianus Marsianus (Fides et Ratio : Jurnal Teologi Kontekstual Seminari Tinggi St. Fransiskus Xaverius Ambon, 2024)
The focus of this discussion is to explore the Catholic Church's efforts to answer Martin Luther's challenge based on the Council of Trent.  The Church was in a dilapidated situation, where there were many irregularities in the life of the Church. Martin Luther came as a reformer, by issuing 95 propositions or theses, which contained a rejection of doctrine, theology and authority in the Church. He also criticized the lives of priests who were thirsty for worldly things. The Church through the Council of Trent tried to answer the challenge of Martin Luther and carry out internal reforms.  To deepen this discussion, the author uses a descriptive qualitative method in the form of a literature study by referring to sources such as books and articles.  The aim is to find out the teachings that were straightened out by the Church in response to Martin Luther's challenge. From this, the author finds that the Church has an open attitude towards Luther's criticism. The Church realized that there were many weaknesses that arose within the Church, and for this reason the Church carried out reforms. However, the Church still maintains its doctrine and teaching of faith, rejecting sola scriptura, sola gratia and sola fidei.